Relationship between Parent’ Social Support and Student Academic Procrastination Completing Assignments at SMAN - Armon Saputra; Khairani Khairani (Universitas Negeri Padang, 2021)
This research is motivated by the phenomenon of students having bad academic procrastination attitudes due to lack of parental social support. This study aims to 1) describe parental social support, 2) describe academic procrastination, and 3) identify the relationship between parental social support and academic procrastination of students completing lesson assignments at SMAN.This research is descriptive and correlational. The population of this study was 401 students at SMAN 1 X Koto Singkarak for the 2019-2020 school year. The sample in this study was 215 students at SMAN 1 X Koto Singkarak for the 2019-2020 school year. The instrument used was a Likert scale instrument. The data is processed using statistical techniques to determine the mean, standard deviation, range, score and percentage. To find the relationship between two variables, the Pearson Product Moment technique was used with the help of the Statistical Product and Service Solution program for Windows Release 20.0.The results of the study revealed that 1) the social support of the parents of students completing lesson tasks at SMAN was mostly in the medium category, 2) the academic procrastination of students completing the assignments at SMAN was mostly in the high category, and 3) there was a negative and significant relationship between the parents' social support. with academic procrastination students complete assignments at SMAN with a correlation level of 0.035. Based on the research findings, it is suggested that Gurun BK / counselors at SMAN can help rationalize students' thinking in completing lesson assignments at SMAN about good parental social support and change the lower academic procrastination attitudes. This is so that students become enthusiastic in achieving their goals and support a better education. In addition, for those who are already married, it is recommended that they be given family guidance with the same material.